Answer:
The value of variable 'x' is 6.
Explanation:
Solving this problem entails of identifying the value for the variable in the equation. We can start by combing the like terms on the left side of the equation. The terms 2 and 1 are the only common terms so these will be the ones we combine and add.
2 + x + 1 = 2x - 3
(2 + 1) + x = 2x - 3
3 + x = 2x - 3
In this step we will use the subtraction property of equality. This means we need to subtract the term 'x' from both sides of the equation.
3 + x = 2x - 3
3 + x - x = 2x - x - 3
3 = x - 3
This next step involves a similar property to the one we used in the last step. It is known as the addition property of equality. This means we need to add 3 to both sides of the equation. Eventually, we will find the value of the variable.
3 = x - 3
3 + 3 = x - 3 + 3
6 = x
It's always best to represent the value of 'x' with 'x' displayed on the left side of the equation.
9 = x
x = 6
We have now reached the 'point of no return' or the point of the equation where we can no longer simplify it any further. This shows that the value of the variable is 6.